Animasi kepentingan pokok terhadap alam sekitar berasaskan augmentasi reality / Siti Aishah Hanawi… [et al.] - Hanawi, Siti Aishah; Hanafiah, Hazlenah; Saat, Nur Zakiah; Jenal, Ruzzakiah; Lee, Si Ting (Universiti Teknologi MARA, Sabah, 2017)
Augmented Reality (AR) is a new technology that uses a computer program for displaying virtual objects in the real world. Using AR in conveying information able to attract the public, especially the younger generation thus, this study discusses the development of animation about the importance of trees towards the environment based on AR technology. This animation is built for the purpose of delivering information on environmental issues through the planting of trees. Various types of multimedia elements such as text, graphics, animation and audio were integrated into the AR animation to enhance the effect of information delivery. Three dimensions animated objects were designed and developed according to the issues of the importance of trees in our lives. Adobe Flash Professional CS6 and Autodesk 3ds Max are two main softwares used in this study. This AR animation is function together with webcam and markers in AR Flip book. Users of this animation can gain new perception of the importance of trees and will appreciate more of the environment.